Cytokeratin expression in epidermal stem cells in skin adnexal tumors - Zhou, Xiaoqiu (Oncol Lett, 2019)
The expression levels of seven types of cytokeratin (CK) in different kinds of skin adnexal tumors were evaluated. One hundred and thirty-two patients with different kinds of skin adnexal tumors admitted and treated in the Department of Dermatology of Dongying People's Hospital from May 2013 to May 2015 were selected and underwent tissue section staining. Another 20 cases of normal skin were enrolled as the control group. The expression levels of the seven types of CK in different kinds of skin appendages were observed and recorded. The expression levels of the seven types of CK in the 132 cases of skin adnexal tumor tissues were different. CK10 was mainly expressed in squamous cell carcinoma, but it was not expressed in basal cell carcinoma. CK19 was expressed in basal cell carcinoma, but its expression was not detected in squamous cell carcinoma. As the degree of differentiation was increased in the epidermis, hair follicle and sebaceous gland, the expressed molecular weight of CK was augmented gradually. The expression levels of five types of CK (namely, CK8, CK10, CK14, CK18 and CK19) could be measured in the squamous cell carcinoma and basal cell carcinoma. Statistical analysis revealed that there were statistically significant differences in the expression levels of these five types of CK in the two cell carcinomas (P<0.05). Five types of CK, i.e., CK7, CK8, CK17, CK18 and CK19, had markedly different expression levels in hair follicle tumor and sweat gland tumor, which were statistically significant (P<0.05). The expression levels of a group of CKs detected by virtue of semi-quantitative analysis via immunohistochemistry can be regarded as one of the important indexes for clinical diagnosis of skin adnexal tumors.